Indicadores de qualidade de grãos de soja cultivada em terras baixas - Ody, Lissara Polano (2021)
The interest in soybean cultivation in lowlands, where irrigated rice is predominantly cultivated, has increased, despite being a challenging environment that imposes strong instabilities to the soybean cultivation. This cultivation in rotation with irrigated rice is progressing because mitigation strategies for different factors limiting the growth of soybean plants in lowland soils are applied to allow increasing the yield and crop grain quality. More information about the composition of soybean cultivated in lowlands is needed. Therefore, this study aimed to evaluate the influence of growing conditions of soybean in lowlands on the quality parameters of grains, such as productivity, protein, carbohydrate and ash contents, oil yield and composition in terms of fatty acids, and chemical composition of grains in terms of macro and micronutrients. The sowing was carried out in lowlands at the Regional Research Station of Cachoeira do Sul (RS) (latitude 29º 43' 23 '' South and longitude 53º 43' 15 '' West) in partnership with the Instituto Rio Grandense do Arroz. For the experimental tests, grain samples were obtained under different growing conditions: cultivar DM 61I59 IPRO, harvest period of 2018/2019, two sowing times (November and December), three levels of fertilization (medium, high, and very high), and two types of soil preparation (scarified and non-scarified). Productivity indices are at satisfactory levels. The sowing date in November tends to positively influence the grain yield and soil scarification tends to contribute to higher yields of protein and oil. Carbohydrates constitute the highest percentage of content in grains. Regarding the oil composition, the main fatty acids, such as palmitic acid (C16:0) and linoleic acid (C18:2), were not influenced by the treatments. However, for oleic acid (C18:1), the best percentages are related to the sowing date in November. The macronutrients potassium (K), phosphorus (P), magnesium (Mg) and sulfur (S) and the micronutrient zinc (Zn) did not show sensitivity in the imposed treatments. For nitrogen (N) and copper (Cu), soil scarification allows higher levels of absorption by soybeans. Regarding the nutrients iron (Fe) and manganese (Mn), the treatments did not significantly influence their contents to have statistical differences at a significance level of 95%. The main quality indicators, such as protein and oil content, showed an average content (wet basis) of 17.14% and 14.74%, respectively.